Կարապետ Կոստանեան - Խմբ.՝ Առաքել Առաքելյան (1944-1948); Լևոն Կիսիբեկյան (1948-1950); Աշոտ Աբրահամյան (1950-1955); Առաքել Առաքելյան (1955-1956); Արթուն Հատիտյան (1956-1982); Պարգեւ Շահբազյան (1983-1984); Երվանդ Մելքոնյան (1985-1993); Տ. Ասողիկ եպս. Արիստակեսյան (1994-1996); Տ. Բագրատ աբղ. Գալստյան (1996-1998); Մարիամ Վարդանյան (պաշտոնակատար) (1998-1999); Տ. Արշակ աբղ. Խաչատրյան (պաշտոնակատար) (1999); Անդրանիկ Զեյթունյան (2000-2001); et al. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В публикации епископа Геворга Сарояна «К мемуарам Карапета Костаняна «Отрывки из монашеской жизни Святого Эчмиадзина» преставляется материал об истории монашеской жизни братии Первопрестольного, о быте и облачении, об уставе и нравах, о правилах, координирующих внутренние взаимоотношения среди монахов. The publication by Bishop Gevorg Saroyan of Karapet Kostanyan’s Scenes from the Monastic Life of Holy Etchmiadzin provides access into the history of monastic life in Saint Etchmiadzin at the dawn of the twentieth century, including daily life, manners and customs, and the norms governing human relationships.
Keywords: Biography; Auxiliary Sciences of History; Christianity; History of the Armenian Church